Prevalence and Clinical Significance of Mesenteric Artery Stenosis in Elderly Patients with Acute Abdomen - Pengermä, Pasi; Palm, Erik; Bako, Eszter; Venesmaa, Sari; Karjalainen, Jari; Saari, Petri; Ukkonen, Mika; Kärkkäinen, Jussi M. (Elsevier BV, 2026)
Objective:
To investigate the prevalence of mesenteric artery stenosis and its association with acute mesenteric ischemia (AMI) among elderly patients presenting to the emergency department with acute abdominal pain.
Methods:
This single-center retrospective cohort study included 500 consecutive patients aged ≥65 years who underwent contrast-enhanced computed tomography in the emergency department owing to acute abdominal pain between 2013 and 2014. Imaging data were retrospectively evaluated by a consultant interventional radiologist for 50% or greater stenosis of the superior mesenteric artery (SMA), celiac artery (CA), and inferior mesenteric artery (IMA). The main outcomes of interest were the prevalence of atherosclerotic mesenteric artery stenosis in patients with acute abdominal pain, the prevalence of AMI in patients with mesenteric artery stenosis, and later presentation of mesenteric ischemia until the end of the follow-up, August 2025.
Results:
Altogether, 123 patients (25%) had a mesenteric artery stenosis. Fifty-nine patients (12%) had ≥50% stenosis of the SMA, of whom 28 (5.6%) had 50% to 69% SMA stenosis and 31 (6.2%) had ≥70% SMA stenosis or total occlusion. In patients with SMA stenosis, a concomitant CA stenosis was recorded in 22 patients (37%) and 11 (19%) had a three-vessel disease involving the SMA, CA, and IMA. Forty patients (8.0%) had multivessel stenosis (SMA + CA, SMA + IMA, CA + IMA or SMA + CA + IMA). The prevalence of SMA stenosis increased with age; it was observed in 22 (6.9%) patients aged 65 to 79 years and in 37 (20%) patients aged ≥80 years. There were 14 patients (2.8%) with isolated 50% to 69% stenosis of the SMA of whom none had AMI at presentation; patients 9 (1.8%) had isolated ≥70% SMA stenosis of whom 2 (22%) presented with AMI. Of all patients with ≥70% SMA stenosis, 12 of 31 (39%) presented with AMI, and 12 of 40 (30%) with any multivessel stenosis presented with AMI. One of the patients with incidental mesenteric artery stenosis (ie, no AMI at presentation) developed symptomatic mesenteric ischemia during follow-up.
Conclusions:
Mesenteric artery stenosis is a relatively common clinical problem in elderly patients with acute abdomen. The risk of AMI is significant in emergency room patients with ≥70% SMA stenosis and involvement of other mesenteric arteries (multivessel disease). Occurrence of later symptoms seems to be rare in patients with incidental asymptomatic mesenteric artery stenosis.